If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 18 = 5(5x + 7) Reorder the terms: 18 + 26x = 5(5x + 7) Reorder the terms: 18 + 26x = 5(7 + 5x) 18 + 26x = (7 * 5 + 5x * 5) 18 + 26x = (35 + 25x) Solving 18 + 26x = 35 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 18 + 26x + -25x = 35 + 25x + -25x Combine like terms: 26x + -25x = 1x 18 + 1x = 35 + 25x + -25x Combine like terms: 25x + -25x = 0 18 + 1x = 35 + 0 18 + 1x = 35 Add '-18' to each side of the equation. 18 + -18 + 1x = 35 + -18 Combine like terms: 18 + -18 = 0 0 + 1x = 35 + -18 1x = 35 + -18 Combine like terms: 35 + -18 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 6-3x-11x+4= | | 9x-5x=6x+7x | | 9x+9=2x+9 | | (5x+8)-(7+4x)=8 | | 7-7(3c-2)+4(c-7)+3c=0 | | 25-2x=17+2x | | 11x+7y=2 | | 8n=-160 | | (5x+8)-(7+4y)=8 | | 5=x-17 | | 24=6(5-2a) | | -29=-25+r | | 0=1600-60x | | -9=m-(-5) | | -9/12-(-7/4) | | 7y-3x= | | 15x+(-4x)= | | 1/7*1/6 | | 2xy/5y | | -480=20x | | 4-p=5p+16 | | 522=29x | | 4x+5-2x=-19 | | 3[4x-(2x-7)]= | | a/1/a2= | | 1=v-(-12) | | 5x+12=3x-23 | | 8/9*(-1/8)= | | -3+a=26 | | -5(1+5n)=120 | | (5x+2)(5x-1)=0 | | 3x+y-4x= |